Pelatihan kesehatan terhadap pengetahuan tentang perawatan luka pasca operasi - Eka Yudha Chrisanto; Nur Afni; Andoko Andoko (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2019)
Impact of health educational program upon nurses' knowledgeTowards postoperative wounds care in Lampung-Indonesia Background: The surgery in Indonesia ranks 11th out of 50 treatments for disease patterns in hospitals in Indonesia, which is an estimated 32% of them were laparotomy. The number of abdominal surgical cases in Lampung Province in 2017 was (28.95%) and increased in 2018 by (32.45%).Purpose: Know the effect of health training in knowledge and surgical wound management.Methods: This type of study was quantitative, with the Pre-Experiment design and the design one group pre test - post test. The populations were all of postoperative patients and samples of 34 people with a total sampling technique. Data collection uses questionnaire sheets and the statistical test used dependent t-test.Results: The average knowledge about postoperative wound care before being given health training of 14.18 and a standard deviation of 1.749. The average knowledge about postoperative wound care after being given health training of 17.06 and a standard deviation of 3.142, with p-value = (0,000 <0,05).Conclusion: There was the effect of health training in knowledge and surgical wound management. Health workers are expected to be able to apply the provision of health training to postoperative patients to improve patient knowledge in subsequent care and be used as a reference for making policies regarding the provision of health training to postoperative patients. Keywords: Health educational program; Nurses; Knowledge; Postoperative wounds care Pendahuluan: Tindakan operasi di Indonesia menempati urutan ke-11 dari 50 pertama penanganan pola penyakit di rumah sakit se-Indonesia yang diperkirakan 32% diantaranya merupakan tindakan bedah laparatomi. Jumlah kasus bedah abdomen di Provinsi Lampung pada tahun 2017 sebesar (28,95%) dan meningkat pada tahun 2018 sebesar (32,45%).Tujuan: Diketahui pengaruh pelatihan kesehatan terhadap pengetahuan tentang perawatan luka pasca operasi.Metode: Jenis penelitian kuantitatif, dengan rancangan penelitian Pra Experiment dan pendekatan one group pre test - post test design. Populasi seluruh pasien post operasi dan sampel sebanyak 34 orang dengan teknik total sampling. Pengumpulan data menggunakan lembar kuesioner dan menggunakan uji dependent t-test.Hasil: Rata–rata pengetahuan tentang perawatan luka pasca operasi sebelum diberikan pelatihan kesehatan sebesar 14,18 dan standar deviasi sebesar 1,749. Rata–rata pengetahuan tentang perawatan luka pasca operasi sesudah diberikan pelatihan kesehatan sebesar 17,06 dan standar deviasi sebesar 3,142, dengan p-value = (0,000 < 0,05).Simpulan: Ada pengaruh pelatihan kesehatan terhadap pengetahuan tentang perawatan luka pasca operasi. Diharapkan petugas kesehatan dapat mengaplikasikan pemberian pelatihan kesehatan kepada pasien pasca operasi untuk meningkatkan pengetahuan dalam perawatan selanjutnya dan dijadikan referensi untuk membuat kebijakan mengenai pemberian pelatihan kesehatan kepada pasien pasca operasi.